2011
DOI: 10.5581/1516-8484.20110056
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of BCR-ABL levels in chronic myeloid leukemia patients treated with imatinib in the chronic phase

Abstract: BackgroundReal time PCR has become the most common technique to monitor BCR-ABL transcript levels of patients treated with kinase inhibitors. The aim of this study was to evaluate BCR-ABL levels of chronic myeloid leukemia patients treated with imatinib in the chronic phase and correlate the response to therapy and event-free survival.MethodsBCR-ABL levels were measured in peripheral blood cell samples using Real time PCR at diagnosis and then every 3 months after starting therapy with imatinib. Major molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…This result was approximately closed to data reported from Patan hospital in India where optimal hematological response rate was 78% [18], but lower than those reported in Asia including China, Hong Kong, India and Southern Korea with 98%, 100%, 96%, and 100% optimal hematological response respectively [19], and lower than data reported from Brazil (95%) [20], Portugal (95.4%) [21], Malaysia (93.2%) [22], and Tanzania (91.3%) [23]. where optimal hematological response reached at the end of three months following starting therapy.…”
Section: Discussionsupporting
confidence: 50%
“…This result was approximately closed to data reported from Patan hospital in India where optimal hematological response rate was 78% [18], but lower than those reported in Asia including China, Hong Kong, India and Southern Korea with 98%, 100%, 96%, and 100% optimal hematological response respectively [19], and lower than data reported from Brazil (95%) [20], Portugal (95.4%) [21], Malaysia (93.2%) [22], and Tanzania (91.3%) [23]. where optimal hematological response reached at the end of three months following starting therapy.…”
Section: Discussionsupporting
confidence: 50%
“…BCR-ABL1 transcripts were measured in the peripheral blood by real-time quantitative polymerase chain reaction (RQ-PCR) at baseline and then every 3 months using procedures described elsewhere with some modifications 11 . First, cDNA was amplified using the ABI 7300 sequence detection system (Applied Biosystems) and TAQMAN Universal Master Mix in a final reaction volume of 25 μL according to the instructions recommended by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“… 4 De Lavallade et al, Silveira and Machado et al found this level of response in 39.0%, 37.1% and 40% of patients, respectively. 15 , 16 , 17 In the prospective and sequential study of de Lavallade et al, patients achieved MMR between two and 73 months (median: 15.7 months) after starting treatment. 15 MMR was achieved with a median time of 18 months (6–78 months) according to Silveira, but his study included too few patients with molecular assessments ( n = 39).…”
Section: Discussionmentioning
confidence: 99%
“…16 Machado et al found this response level between 0.4 and 31 months of treatment (median: 8.5 months). 17 In this time interval, 31.7% (26/82) were included in the warning signs group ( BCR - ABL1 IS >0.1 and ≤1%), and 23.2% (19/82) in the treatment failure group as the number of transcripts >1% according to the ELN criteria. 5 …”
Section: Discussionmentioning
confidence: 99%